Psicoterapia online em pessoas idosas com sintomas de ansiedade e depressão - Pedot, Rafaela Andréia (2023)
In the COVID-19 pandemic, old people who had symptoms of anxiety and depression were largely affected by isolation and social distancing, which motivated the search for mental health care online. In this context, there was an increase in the offer of intervention services based on online Cognitive Behavioral Therapy (CBT) for the old population, making it necessary to verify the scope and limits of these services. This study aimed to gather empirical evidence on the effects of online CBT in older people with symptoms of anxiety and depression. In view of the proposed objective, a study entitled “Online Cognitive Behavioral Therapy for Older People with Anxiety and Depression: Systematic Review” was conducted, according to the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses PRISMA, using Health Sciences Descriptors , in the Virtual Health Library databases (BVS), PubMed, CAPES, Science Direct, and in the SciELO library. The study selection process was performed by three reviewers. The inclusion criteria used were articles published between 2017 and 2022 with samples that included old people aged 60 years and over, published in Portuguese, English, and Spanish in peer-reviewed scientific journals, and open access. Exclusion criteria were duplicate articles, unfinished studies, studies in progress, literature reviews, theses, dissertations, comments, book chapters, reviews, conference proceedings or those that are not consistent with the theme, and that present a high risk bias. The search strategies resulted in 26 articles in BVS, 19 in PubMed, 17 in CAPES, 12 in Science Direct, and zero in the SciELO library. A total of 74 articles were found, and of these, 69 articles were excluded for not meeting the inclusion criteria or for being duplicated, totaling 5 articles included in this SR. All articles were carried out internationally. The sample size surveyed varied extensively, from 47 to 216 participants. The use of CBT through an online resource (internet) showed positive and promising results, with a reduction in symptoms of anxiety and depression in the researched population. As for the general risk of bias of the articles in this study, the results revealed a minimal possibility for this factor, since the scores presented are greater than 20 and the studies failed to complete only one item of the scale in the evaluation of each item of risk of bias, which increases the evidence for this RS. The results of the present study demonstrate the state of the art on the positive effects of online CBT in old people with symptoms of anxiety and depression, so far. Finally, there is a need to develop research on the use of CBT in the online modality in Brazil; to examine the effectiveness of this modality of intervention in the long term and in different health conditions of older adults, since greater involvement with online assistance programs can optimize care for this population and lead to a reduction in the burden of common mental health problems.